Curvature dependence of quantum gravity - Christiansen, Nicolai; Falls, Kevin; Pawlowski, Jan M.; Reichert, Manuel (Arxiv, 2017)
We investigate the phase diagram of quantum gravity with a vertex expansion about constantly-curved backgrounds. The graviton two- and three-point function are evaluated with a spectral sum on a sphere. We obtain, for the first time, curvature-dependent UV fixed point functions of the dynamical fluctuation couplings